Multi-omics analysis explore the mechanism of deoxynivalenol inhibiting rabbit appetite through microbial-gut-brain axis - Xuejun Yuan; Wenjie Chen; Rui Li; Huijun Guo; Chunyang Wang (Ecotoxicology and Environmental Safety, 2025)
Deoxynivalenol (DON) is one of the most prevalent mycotoxins and can induce weight loss and vomiting in animals. This study aimed to elucidate the molecular mechanisms underlying DON-induced anorexia in rabbits through the microbial-gut-brain axis. A total of forty rabbits were randomly divided into a DON group and a control group, receiving 1.5 mg/kg.BW of DON and an equivalent volume of saline daily via intragastric administration, respectively. The pre-treatment period lasted for 7 days, followed by a formal experimental period of 24 days. The findings revealed that DON exposure significantly reduced daily food intake and weight gain, leading to intestinal apoptosis and barrier injuries. 16S rRNA sequencing data indicated that DON exposure decreased the diversity and richness of cecal microflora, suppressed probiotic populations, and disrupted host lipid metabolism. RNA-Seq and iTRAQ data were used to cross-analyze the shared differentially expressed genes (DEGs) and differentially expressed proteins (DEPs) in the hypothalamus and jejunum, along with their shared enrichment pathways, indicating that TNF-α, NF-κB, and NPY may play pivotal roles in DON-induced anorexia. qRT-PCR and Western blotting results confirmed significant increases in mRNA and protein expression levels of TNF-α, NF-κB and 5-HT2A in both the hypothalamus and jejunum. In conclusion, DON ingestion in rabbits can disrupt the intestinal barrier, up-regulate the expression of IFN-γ, TNF-α, NF-κB, and 5-HT2A in the intestine, and trigger an immuno-inflammatory response in the hypothalamus via the microbial-gut-brain axis, ultimately resulting in appetite suppression and weight loss.